2005
DOI: 10.19030/tlc.v2i5.1811
|View full text |Cite
|
Sign up to set email alerts
|

From University To School: Preparing Pre-Service Teachers For The Real World

Abstract: Much of the literature on programs of pre-service teacher education highlights the disparity between what is learned at university and what is actually required in the classroom. This paper outlines a new philosophy of teacher training adopted by the Faculty of Education and Creative Arts at Australia’s Central Queensland University. It describes the design, content and operation of a new practicum program, where in a unique partnership between the university and the education community in which it operates, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Many studies demonstrate that the practicum component of teacher education must be more closely guided by accredited professional standards and that its costs and resources must be more carefully considered (Apple, 2001;Wise & Leibbrand, 2001;Huntly, 2005;Ure & Gough, 2009;Sulistiyo, Mukminin, Abdurrahman, & Haryanto, 2017).…”
Section: Quality Standards For Practicum Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies demonstrate that the practicum component of teacher education must be more closely guided by accredited professional standards and that its costs and resources must be more carefully considered (Apple, 2001;Wise & Leibbrand, 2001;Huntly, 2005;Ure & Gough, 2009;Sulistiyo, Mukminin, Abdurrahman, & Haryanto, 2017).…”
Section: Quality Standards For Practicum Trainingmentioning
confidence: 99%
“…This necessitates increasing credit hours for the practicum and allocating several hours to a theoretical course for the practicum. This was also emphasized by Huntly (2005) who concluded that "practicum is preceded by an extensive course of preparatory lectures and tutorials that cover important aspects of the work of teachers. Students are provided with detailed insights into teaching elements including handwriting, planning, classroom management, ethical behavior, and reflective practice" (p. 19).…”
Section: The Second Practicum Aspect: Contentmentioning
confidence: 99%